Impacts on spatial variability of soil density and porosity as a function of the transformation of forest into pasture in Vale do Jamari, Rondônia (Research, Society and Development, 2022)
With the replacement of forest areas by agricultural crops or pastures, changes occur in soil attributes, such as increased soil density, breakdown and loss of organic matter. The present work aimed to evaluate the impacts on the spatial variability of the attributes of soil density, total porosity, macro and microporosity in an area that suffered alteration from forest to pasture in Vale do Jamari, RO. The experiment was carried out in soils under natural and altered environments, found in the Western Amazon, Vale do Jamari, State of Rondônia. The areas are located in the central - northern portion of the state of Rondônia, in the municipality of Ariquemes. A sampling grid was established in each land use system. The dimensions of each mesh were 50 x 100 m, making a total of 66 sampling points in each mesh. At the crossing points, soil samples with preserved structure were collected using a volumetric ring at a depth of 0.0-0.05 m, 0.05-0.10 m and 0.10-0.20 m. The physical attributes were evaluated: soil density, macro and microporosity and total porosity. Statistical analyzes were processed using the Surfer 8.0 program. For the hypothesis of normality of the data, it was tested by the Kolmogorov-Smirnov test, available in the statistical program Statistica 7.0. The pasture showed moderate variations in its physical attributes in relation to the native forest. The values ​​of physical attributes of soil density were higher in the pasture area. The forest showed greater homogeneity of spatial data, with greater ranges.